Histopathology of Dryas octopetala leaves co-infected by Subanguina radicicola and Aphelenchoides sp. and molecular caracterization of the nematodes - Bland, K P; Fanelli, Elena; Troccoli, Alberto; Vovlas, Nicola (European Journal of Plant Pathology, 2018)
During a survey, in the Perthshire hills, Scotland, altitude 800–900 m a.s.l., samples of Dryas octopetala leaves showing concomitantly symptoms of galls and discolored spots, were collected. Several nematodes, juveniles and adults, were isolated by dissecting foliar tissues. Two species of nematodes, recovered and identified at morphological and molecular level as Aphelenchoides sp. and Subanguina radicicola, are herein reported. The most significant diagnostic characters for species identification of nematode specimens extracted from Dryas leaf galls fitted well with those previously reported for S. radicicola. Concerning the Aphelenchoides sp., the diagnostic characters were very similar to those reported for A. ritzemabosi.The ITS and the D2-D3 expansion domain analyses confirmed the presence of S. radicicola from galls, while Aphelenchoides specimens from discoloured leaf areas), despite the morphological similarity with A. ritzemabosi, were genetically distinct from A. ritzemabosi based on two genomic regions (LSU and ITS). The 18S rRNA gene (SSU) was only amplified in S. radicicola. Phylogenetic analyses using ITS and LSU sequences placed S. radicicola with other populations of the same species and Aphelenchoides sp. with species of the same genus. The histopathology, caused by both endoparasites in naturally infected leaves, was examined via serial sections mounted on glass slides. Green Dryas leaves infected by Aphelenchoides sp. appeared discolored (yellowish spots), slightly deformed with a population density of four specimens/cm2 per single leaf blade. Dryas octopetala leaves infected by S. radicicola showed an average of three galls/leaf, located randomly, mainly at the upper leaf edge. Dissected galls contained a central cavity with a variable number of adult females (3–6)/gall and males, together with several immature females, juvenile stages and eggs. The present study reports on a new host plant and an undescribed type of sedentary parasitism of the root-gall nematode, S. radicicola on D. octopetala leaves with the concomitant infection of specimens of Aphelenchoides sp.